Consumption of Plastic and Sustainability Efforts of Nike towards Green Environment - Mukesh Singh Almiya; Daisy Mui Hung Kee; Muhammad Zaki Bin Haron; Muhammad Izham Bin Nasharudin; Muhammad Muaz Bin Mohd Nasruddin; Muhammad Ezzat Wafiy Bin Mohd Johari (AIBPM Publisher, 2020)
Over the recent year, the consumption of plastic in all sorts of organization has been rising to an alarming rate, especially as people now use plastic to wrap material, carrying goods in supermarket or even while drinking (straw). Additionally, plastic is also highly used in packaging and manufacturing industries, especially for furniture, electronic casing and more. Nike itself has a part to play to reduce the rate in order to sustain a safe rate of plastic consumption. Plastic consumption is highly inequitable, with extremely high and wasteful levels in some countries contrasting with vanishingly small consumption levels in others. It is undeniable that people have to start reducing their consumption levels in order to achieve a low overall demand.